Głos kobiet: jaka ma być nowa Europa? - Jakubowska, Teresa; Barański, Jan (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
The author states that formally Poland is not a religious state; however, the country evidently shows signs of a religious state. To support this argument the author points out many examples: the influence of the church on the legal system, education – this is the reason why women are discriminated (anti-abortion law), the favourable treatment of the clergy by the courts, religious instructions at public schools and kindergartens, the absence of school lessons on the human body and it’s pro-creation purposes, situation in the media, the growing influence of the clergy on the army, the funding of the church from the state budget.